ANALISA KETERSEDIAN ALOKASI KANAL RADIO KOMUNITAS DI KOTA DENPASAR - Estry Nurya Savitri; Dewa Made Wiharta; Gede Sukadarmika (Jurnal SPEKTRUM, 2020)
In this study aims to analyze the use of Community radio frequency (Rakom) in Denpasar and byanalyzing the number of channels allocated frequency and the amount of authorized community radioauthorization in the city of Denpasar. It is hoped that the study is expected to give an overview of howavailability community radio channels in Denpasar City area. To be able to avoid interference in theservice area on radio community broadcasts in the city of Denpasar. Conducted analysis andsimulation of mapping of new LPK Radio services (community broadcasting institutions). Themeasured parameters include the calculation of the Budget link and the measurement results obtainedin the field which is then compared with the theory. Based on the results of simulated analysismapping and calculations used, in the area of Denpasar city there can only be 2 (two) radiocommunities.